Tuning IgE: IgE-Associating Molecules and Their Effects on IgE-Dependent Mast Cell Reactions - Tomoaki Ando; Jiro Kitaura (Cells, 2021)
The recent emergence of anti-immunoglobulin E (IgE) drugs and their candidates for humans has endorsed the significance of IgE-dependent pathways in allergic disorders. IgE is distributed locally in the tissues or systemically to confer a sensory mechanism in a domain of adaptive immunity to the otherwise innate type of effector cells, namely, mast cells and basophils. Bound on the high-affinity IgE receptor FcεRI, IgE enables fast memory responses against revisiting threats of venoms, parasites, and bacteria. However, the dysregulation of IgE-dependent reactions leads to potentially life-threatening allergic diseases, such as asthma and anaphylaxis. Therefore, reactivity of the IgE sensor is fine-tuned by various IgE-associating molecules. In this review, we discuss the mechanistic basis for how IgE-dependent mast cell activation is regulated by the IgE-associating molecules, including the newly developed therapeutic candidates.